Foreign exchange regulation act, 1973 [Act XLVI of 1973] - Roy, S.R. (Calcutta, 1986)
AN ACT to consolidate and amend the law regulating certain payments, dealings in foreign exchange and securities, transactions indirectly affecting foreign exchange and the import and export of currency and bullion, for the conservation of the foreign exchange resources of the country and the proper utilisation thereof in the interests of the economic development of the country.
Keywords: Foreign exchange-law and legislation